Answer:
Simplifying
3(2x + 1) + 2(2x + 1) + 7 = 42 + -5x
Reorder the terms:
3(1 + 2x) + 2(2x + 1) + 7 = 42 + -5x
(1 * 3 + 2x * 3) + 2(2x + 1) + 7 = 42 + -5x
(3 + 6x) + 2(2x + 1) + 7 = 42 + -5x
Reorder the terms:
3 + 6x + 2(1 + 2x) + 7 = 42 + -5x
3 + 6x + (1 * 2 + 2x * 2) + 7 = 42 + -5x
3 + 6x + (2 + 4x) + 7 = 42 + -5x
Reorder the terms:
3 + 2 + 7 + 6x + 4x = 42 + -5x
Combine like terms: 3 + 2 = 5
5 + 7 + 6x + 4x = 42 + -5x
Combine like terms: 5 + 7 = 12
12 + 6x + 4x = 42 + -5x
Combine like terms: 6x + 4x = 10x
12 + 10x = 42 + -5x
Solving
12 + 10x = 42 + -5x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '5x' to each side of the equation.
12 + 10x + 5x = 42 + -5x + 5x
Combine like terms: 10x + 5x = 15x
12 + 15x = 42 + -5x + 5x
Combine like terms: -5x + 5x = 0
12 + 15x = 42 + 0
12 + 15x = 42
Add '-12' to each side of the equation.
12 + -12 + 15x = 42 + -12
Combine like terms: 12 + -12 = 0
0 + 15x = 42 + -12
15x = 42 + -12
Combine like terms: 42 + -12 = 30
15x = 30
Divide each side by '15'.
x = 2
Simplifying
x = 2
Explanation: